Pengetahuan dan Sikap Orang Tua Meningkatkan Kepatuhan Protokol Kesehatan Anak Prasekolah Saat Bermain: Parental Knowledge and Attitude Improves Preschool Child Health Protocol Compliance While Playing - Alya Marwah; Eka Rokhmiati; Irma Herliana (Dohara POAJ, 2021)
Introduction: Children are one of the unconscious sources of Covid-19 transmission. Therefore, parents should have knowledge, a good attitude towards children's c ompliance in implementing health protocols, especially when playing. Methods: This study design used a quantitative cross-sectional approach to 50 parents who have preschool aged children. The method of collecting data on children's knowledge, attitudes and compliance uses a questionnaire via google form which is distributed through the whatsapp group. Results: 30 (60%) had poor knowledge, 32 (64%) negative attitudes and 33 (66%) children who did not comply with the Chi-Square test results on parental knowledge were obtained (p = 0.005) and on the attitudes of parents with (p = 0.000). This means that there is a significant relationship between the knowledge and attitudes of parents and compliance with the health protocols of preschool children while playing during the Covid-19 pandemic in the Gadog Pandansari Region. Discussion: Parents' knowledge and attitudes about health protocols affect the compliance of preschool children in playing in the Gadog Pandansari area. It is hoped that parents can take a stand to direct their children to implement better health protocols.